KUALITAS PELAYANAN PERSEMAYAMAN ANGGOTA KORPS PEGAWAI REPUBLIK INDONESIA DI LINGKUNGAN PEMERINTAH DAERAH PROVINSI SULAWESI TENGAH - Ocktaviana, Vita; Mangasing, Nasir; Aksan, Sitti Chaeriah (Katalogis, 2021)
This research aims to analyze the service quality of Funeral Home of the Member of the Employee Corps of the Republic of Indonesia in Central Sulawesi Province. He informants of the research were 6 people. The data were gathered through observation, interview, and documentation. The data were analyzed qualitatively through Miles and HubermanÂ  and Saldana approach namely data collection, data condensation, and drawing conclusion. The research results show that 1. Physical evidence indicates that physical facilities at Employee Corps of the Republic of Indonesia in Central Sulawesi Province are not sufficient. 2. The reliability of the ability of the Employee Corps of the Republic of Indonesia in Central Sulawesi Province to provide service as promised in accurate and accountable way with punctuality parameter, the same service for everything without mistakes have not been running well, the Employee Corps of the Republic of Indonesia in Central Sulawesi Province will show a symphatetic, and a high accuracy in providing funeral home service. 3. Responsiveness is a quick and accurate response given by the Employee Corps of the Republic of Indonesia in Central Sulawesi Province have not been implemented well although there is already clear information. 4. Assurance covers knowledge, politeness, and ability ofÂ  the Employee Corps of the Republic of Indonesia in Central Sulawesi Province to create trust has been running well. 5. Empathy is by providing sincerity attention individually or personally given by the Employee Corps of the Republic of Indonesia in Central Sulawesi Provincen and trying to understand the desire. By having understand and knowledge, understand specifically, and have a comfortable time have been implemented properly.